Congenital hypothyroidism: a case report - Anak A Maswiryati; Nyoman Westra (Indonesian Pediatric Society Publishing House, 2016)
Hypothyroidism resulted from deficiency of thyroid hormone production due to a defect in thyroid gland. The disorder may be manifested earlier. When symptoms occur after a period of normal function of thyroid gland, the disorder may be either truly "acquired" or only appear as a variety of congenital defects in which the manifestation of the deficiency is delayed. Normal level of triiodothyronine (T3) in children is 100-260 ng/dl, thyroxin (T4) 7.3 - 15 mg/dl and thyroid-stimulating hormone (TSH) 2-10 mU/mL. 1,2 The age at which symptoms appear depends on the impairment degree of thyroid function. In many cases, the deficiency of thyroid hormone is severe, and symptoms tend to develop in the early weeks of life. 1,3 The prevalence of congenital hypothyroidism has been found to be 1 in 4,000 infants world wide; it is lower in Japan (1 in 5,500 infants) and in African American population (1 in 32,000 infants). Most infants with congenital hypothyroidism are asymptomatic at birth, even when there is a complete agenesis of the thyroid gland. 1,3 But in other cases, during the first few months of life, the symptoms of hypothyroidism such as feeding problems, failure to thrive, constipation, hoarse cry, and somnolence usually can be found. 1,3,4 The purpose of this study is to report a case of congenital hypothyroidism in a 14 months old child.